2023
DOI: 10.1007/s13399-023-04478-1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of siloxanes from biogas: recent advances in catalyst reusability and water content effect

Abstract: The valorization of biogas as a renewable energy source faces a major obstacle regarding its purification. Siloxane is one of the impurities that cause problems such as damages to equipment of combustion engines, turbines, and boilers used for biogas conversion to heat and electricity. In this review, adsorption for siloxane removal is widely discussed, with two specific approaches: adsorbents sensitivity to water and regeneration, two essential points for industrial application. Thus, determining factors in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 92 publications
0
1
0
Order By: Relevance
“…An undoubtedly significant issue is the question of the stability and reusability of the catalyst. As observed, in most of the studies in this review, the stability and reusability of the catalyst have not been investigated except for a few works [120,121,[123][124][125]127]. Generally, these studies showed good results for long operation times in the range of a few hours.…”
Section: Stability and Reusability Of Catalystsmentioning
confidence: 98%
See 1 more Smart Citation
“…An undoubtedly significant issue is the question of the stability and reusability of the catalyst. As observed, in most of the studies in this review, the stability and reusability of the catalyst have not been investigated except for a few works [120,121,[123][124][125]127]. Generally, these studies showed good results for long operation times in the range of a few hours.…”
Section: Stability and Reusability Of Catalystsmentioning
confidence: 98%
“…MOFs offer considerable opportunities for the incorporation of active sites for catalysis that mimic methane monooxygenases, with high tailorability of the pore structures and environmental conditions in the proximity of the active sites. In this regard, there is already a considerable amount of literature in which various aspects of MOF are well reviewed: synthesis and post-synthetic modifications [103][104][105], active sites and their characterization [106], structure [107][108][109][110], the inclusion of defects [111][112][113][114], water stability [115,116], scale-up of synthesis [117][118][119], multiple functionalities [120,121], application for CO 2 and biomass conversion [122][123][124][125]. In this review, a deep comparison of the MOF-based catalysts for the conversion of methane to methanol is performed in terms of methane conversion, methanol selectivity, and space-time yield (STY) (Table 2).…”
Section: Nanomaterials Used With Mofs 431 General Characteristicsmentioning
confidence: 99%
“…Raman spectroscopy (Figure 2g) is an experimental technique which is sensitive to the carbon state; therefore, it can be used to analyze the structure of APCs. The characteristic peaks in the Raman spectrum of carbon materials are mainly D and G peaks, where the D peak is attributed to the disordered or defected sp 3 -bonded carbon, and the G peak originates from the in-plane vibrations of the sp 2 -bonded carbon [40]. The intensity ratio of D and G peaks (I D /I G ) presents the graphitization degree of carbon materials.…”
Section: Basic Characterization Of Apc and Aptms@apc−0125mentioning
confidence: 99%
“…In addition to containing methane, biogas comprises some other components, such as carbon dioxide (CO 2 , 30–50 percent vol. ), hydrogen sulfide (H 2 S, 5000–10,000 ppm), ammonia (NH 3 , 100 ppm), and volatile methyl siloxanes (VMS, traces, 3–150 mg m −3 ) [ 3 , 4 , 5 ]. With the improvement of urbanization, silicone materials are widely used, and more than 90% of all the VMS entering the environment end up in the atmosphere [ 6 ].…”
Section: Introductionmentioning
confidence: 99%